Correlation of Growth Components and Yield of Jack Bean (Canavalia ensiformis) and Velvet Bean (Mucuna pruriens) Treated with NPK Fertilizer - Fatiharizqi, Muhammad; Subhan Abdurrazaq, Difaa Ali; Maulana, Wahyudi; Nur Auliya, Sukma; Trisnaningsih, Umi (Ann Publisher, 2025)
Background. The correlation between growth traits and yield is essential information in a plant breeding program. Jack bean and velvet bean are two legume species that have the potential to be a source of vegetable protein to replace soybeans. Aims. This study seeks to ascertain the relationship between growth component qualities and yield in jack and velvet beans subjected to varying amounts of NPK fertilizer. Methods. The research was conducted at Nanggela Village, Mandirancan District, Kuningan Regency, from June to November 2024. The administered treatments included of NPK fertilizer applications (150, 225, 300, 375, and 450 kg/ha) in conjunction with bean species (jack bean and velvet bean). The observed growth components included plant height, leaf count, stem diameter, root volume, root length, nodule count per plant, leaf area index, and relative growth rate. The observed yield components included the number of pods per plant, pod weight per plant, 100-seed weight, seed weight per plant, and seed weight per plot. The data were examined utilizing the Pearson Correlation Test to ascertain the strength of the association between growth components and yield, as well as yield components. Result. The research findings indicate a correlation among both species' stem diameter, root volume, leaf area index, pod weight, seed weight, seed count, and 100-seed weight. Conclusion. The yield components, including the number of pods per plot, the number of pods per plant, the weight of pods per plot, and the weight of pods per plant, are significantly correlated with the weight of 100 seeds and the weight of seeds per plot in the velvet bean. Implementation. The character of stem diameter and leaf area index can be used to select high-yielding koro plants. Indirect selection in jack bean can also be done through plant height and leaf number characteristics. In velvet beans, indirect selection can be carried out through yield component traits.